Effects of myo-inositol concentration on growth and pigments of Nannochloropsis oculata culture - DURMAZ, Yaşar; ERBİL, Gökhun Çağatay (Ege University Faculty of Fisheries, 2020)
Inositols are used as growth promoting agents over plants. But microalgae are different from higher plant especially photosynthetic efficiency and productivity. According to the results of this study, myo-inositol addition to the culture medium of Nannochloropsis oculata provides higher cell densities. 100 mg L-1 myo-inositol added experimental group was reached to 1.42 fold cell mL-1, while the 500 mg L-1 myo-inositol added group was reached to 1.28 fold cell mL-1 than the control group. Mean chlorophyll a per cell amounts were calculated for experimental groups and control groups as 0.052 pg cell-1 and 0.053 pg cell-1, respectively. Mean total carotene per cell amounts were calculated for all groups as 0.016 pg cell-1. These results show that no difference was occurred between all groups by chlorophyll a and total carotene amounts per cell. This study shows that myo-inositol use in microalgae production may provide higher yields.
Keywords: carotene; myo-inositol; Nannochloropsis oculata; microalgae; pigments; chlorophyll; 14. Life underwater; 3. Good health